CYTOKINEPRODUCING ACTIVITY OF BLOOD LYMPHOCYTES IN RELATIONSHIP WITH THE TENSION OF IMMUNITY TO DIPHTHERIA AND TETANUS IN PERSONS WITH EPSTEIN-BARR VIRUS INFECTION - Lyadova, Tetyana; Popova, Alisa; Volobueva, Olga; Kozlov, Oleksandr; Dorosh, Diana (Eastern Ukrainian Medical Journal, 2024)
Objective. To study the cytokine-producing activity of lymphocytes in relation to the intensity of immunity to diphtheria and tetanus in persons who have contracted chronic form of Epstein-Barr virus infection. Materials and methods. The activity of lymphocytes in-vitro, the production of cytokines (IL-2, IL-4, IL-5, IL-10, IL-15, IL-21, IL-23) was studied in persons who became ill with chronic form of Epstein-Barr virus infection in comparison with those who did not have a protective level of antibodies to diphtheria and tetanus (16 people – 1-st group) and in people who have a protective level of antibodies to these infections (16 people – 2-nd group). The control group consisted of 20 people. The age of the examinees was 18–22 years. The level of cytokines in the culture medium was measured by ELISA. Spontaneous production of cytokines, induced by FHA and the potential of lymphocytes to produce cytokines were determined. Results: It was established that in individuals of groups 1 and 2 who became ill with EBV infection, there was a decrease in spontaneous and induced production of cytokines - IL-2, IL-4, IL-5, IL-15, IL-21, IL-23 and increased production of IL-10 in comparison with the control group of individuals. In people of group 1, the production level of the main cytokines was probably lower than in people of group 2, and IL-10 was higher. The potential for cytokine production in people of group 1 was probably lower (p<0.05) than in people of group 2 and the control group of people. In individuals of group 1 and group 2, a violation of the balance between cytokines with an activating effect on B-lymphocytes and a suppressive effect was observed. Conclusions: Under the influence of EBV-infection, the activity of lymphocytes to produce cytokines decreases, the potential of cells to produce them decreases, and an imbalance between the regulatory cytokines of antibody formation develops. In persons who have contracted CHEBVI and do not have a protective level of antibodies to diphtheria and tetanus in their blood, the activity of lymphocytes in the production of antibody-stimulating cytokines and the potential for their production is lower, and the imbalance between regulatory cytokines is higher than in persons who have a protective level of antibodies to these infections. A decrease in the activity of lymphocytes, the production of cytokines that regulate antibody formation is one of the factors in the decrease in the level of post-vaccination antibodies in persons who have contracted EBV-infection.